Olympic competition climbing: the beginning of a new era—a narrative review. Issue 15 (9th October 2020) - Lutter, Christoph; Tischer, Thomas; Schöffl, Volker Rainer
Abstract : Climbing as a competition sport has become increasingly popular in recent years, particularly the sub-discipline of bouldering. The sport will debut in the Tokyo Summer Olympic Games. National and international competitions have three disciplines: lead (climbing with rope protection), bouldering (climbing at lower heights with mattress floor protection) and speed (maximum speed climbing on a standardised route in 1-on-1 mode). There is also a 'combined mode' of all three disciplines ( combined ) which forms the Olympic competition format; all competition formats are held on artificial walls. Existing literature describes a predominantly low injury frequency and severity in elite climbing. In comparison to climbing on real rock, artificial climbing walls have recently been associated with higher injury rates. Finger injuries such as tenosynovitis, pulley lesions and growth plate injuries are the most common injuries. As finger injuries are sport-specific, medical supervision of climbing athletes requires specific medical knowledge for diagnosis and treatment. There is so far little evidence on effective injury prevention measures in top athletes, and antidoping measures, in general, requiring further work in this field. An improved data situation regarding high-performance climbing athletes is crucial to ensure that the sport continues to be largely safe and injury-free and to prevent doping cases as extensively as possible.